2011
DOI: 10.1080/00102202.2011.567199
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Effects of Flame Phenomenology on the Wall Temperature Distribution of Mesoscale Nonadiabatic Ducts

Abstract: Infrared thermography was used in order to examine the effects of flame phenomenology in mesoscale ducts on the temperature profile of the duct walls. Rich methane-oxygen mixtures of were burned in straight mesoscale ducts of a circular cross-section. Equivalence ratio was varied to produce different flame behaviors, including externally stabilized flames at the tube exit, stationary flame fronts within the tube, and oscillating flame fronts that propagated within the tube. Infrared thermometry was used in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Studies that examined the flame stability limits and wall temperatures have been examined, but the observed area still tends to be in the area of large equivalence ratio. The flame phenomenon of the circular mesoscale combustor (d=4 mm) has been studied using a methane-oxygen mixture [15]. The study produced a map of flame stability limits and divided into 5 flame modes.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that examined the flame stability limits and wall temperatures have been examined, but the observed area still tends to be in the area of large equivalence ratio. The flame phenomenon of the circular mesoscale combustor (d=4 mm) has been studied using a methane-oxygen mixture [15]. The study produced a map of flame stability limits and divided into 5 flame modes.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…It has been revealed from previous studies [15] that the use of pure oxygen produces a very high flame propagation speed, consequently the flame stability limit shifts to a rich mixture, this is due to the fact that the flame had a flashback at a low equivalent ratio. Improvement effort has been made to delay the occurrence of flashback by using a double narrow slit flame holder [16] which results showed that the flame stability limit can extend to the low equivalent ratio (lean mixture).…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The propagation of premixed flame in a tube constitutes a basic configuration in the buildup of miniaturized combustors. Experiments [4][5][6][7][8][9] have shown that the characteristics of the flame propagation regime are sensitive to various parameters such as transport, thermodynamics and conductive properties, composition mixture and tube geometry.…”
Section: Introductionmentioning
confidence: 99%